Cryosurgery, Intralesional Methotrexate and Imiquimod for Keratoacanthoma: Tuning the Combination - Georgios Gaitanis; Ioannis D. Bassukas (Case Reports in Dermatological Medicine)
Keratoacanthomas (KA) are self-regressing, destructively expanding keratinocyte skin neoplasms typically characterized by sudden onset of explosive growth followed by complete involution. Cryosurgery, intralesional methotrexate and imiquimod have been used alone or in combination of two for the treatment of KA. Presently 3 patients (49, 60, and 65 years old; two females, one suspected with Ferguson-Smith syndrome), with 5 KA (6–24 mm maximal diameter) were treated with the combination of cryosurgery (liquid N2, open spray, 2 cycles of 15 sec each) and intralesional methotrexate (2.5–30 mg cumulative dose) and subsequent daily application of imiquimod (14–35 days). Starting with 4 cryosurgery/intralesional methotrexate sessions and 5 weeks daily imiquimod, to document feasibility and efficacy we progressively reduced the intensity of the treatment to one cryosurgery/intralesional methotrexate (total dose: 5 mg) session and 14 days of daily imiquimod without compromising efficacy. KA stopped growing promptly with sustained clearance after 6–24 months follow up, implicating a huge potential of therapeutic synergy of the employed modalities in the management of KA. We suggest that, optimized, the present three modalities combination (one session mild cryosurgery/low dose, 5 mg intralesional methotrexate and 2 weeks once daily imiquimod) is a promising treatment for KA that merits evaluation in further studies.